Using the PSO algorithm to study the effect of shear stress on an I-shaped section on von Meses stress. - دواي ايهم; ايمن يوسف; حاتم محمودي (Latakia University Journal -Engineering Sciences Series, 2024)
In this research, a section in the form of the letter I of one length, made of steel alloy st 37-2, loaded of [1] KN, and the Von Mises stress generated in the section under the influence of this load was studied. Then the PSO algorithm was used to obtain the optimal dimensions of the studied section that achieve the lowest possible shear stress under the influence of the same load, the inverter program was used to verify the results and determine the value of the von Mises stress for the resulting section.